Guide to managing and maintaining your PC - Andrews, Jean (Thomson/Course Technology, 2003)
The A+ Guide to Managing and Maintaining Your PC, Fourth Edition Introductory by best-selling author Jean Andrews is written expressly for the classroom or effective self-study. With a new chapter on Windows 2000 and coverage on the Linux operating system, this title thoroughly covers the most up-to-date topics in the PC Repair industry. This book helps computer users gain skills required to support and repair their own PC and also covers how a computer works, and how to maintain, troubleshoot, upgrade and repair a PC. This title also serves as an excellent resource for those interested in PC Repair and/or A+ certification